2010
DOI: 10.1063/1.3298371
|View full text |Cite
|
Sign up to set email alerts
|

Role of the triplet state in the green emission peak of polyfluorene films: A time evolution study

Abstract: The blue emission of ethyl-hexyl substituted polyfluorene ͑PF2/6͒ films is accompanied by a low energy green emission peak around 500 nm in inert atmosphere. The intensity of this 500 nm peak is large in electroluminescence ͑EL͒ compared to photoluminescence ͑PL͒ measurements. Furthermore, the green emission intensity reduces dramatically in the presence of molecular oxygen. To understand this, we have modeled various nonradiative processes by time dependent quantum many body methods. These are ͑i͒ intersystem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Moreover, in the presence of heavy metal salts or complexes of transition metals such as Ir, Pd, and Re, there is considerable enhancement of the T-S emission intensity observed due to the spin−orbit coupling effects. 161 Transition metals are known to help in spin crossover processes, 163−166 and here, we refer works on spin-catalysis theory for more details and applications. 167−171 Returning to the discussion on short polyenes it should be noted that the estimated oscillator strengths of the S 0 → T 1 transition for pure species like ethylene, butadiene, and hexatriene are on the order of 10 −101,99,168 that corresponds to a very large radiative lifetime of the T 1 state (from seconds to few minutes) and being devoid of any phosphorescence patterns, because of efficient quenching.…”
Section: Phosphorescence Of Unsaturated and Aromatic Hydrocarbonsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, in the presence of heavy metal salts or complexes of transition metals such as Ir, Pd, and Re, there is considerable enhancement of the T-S emission intensity observed due to the spin−orbit coupling effects. 161 Transition metals are known to help in spin crossover processes, 163−166 and here, we refer works on spin-catalysis theory for more details and applications. 167−171 Returning to the discussion on short polyenes it should be noted that the estimated oscillator strengths of the S 0 → T 1 transition for pure species like ethylene, butadiene, and hexatriene are on the order of 10 −101,99,168 that corresponds to a very large radiative lifetime of the T 1 state (from seconds to few minutes) and being devoid of any phosphorescence patterns, because of efficient quenching.…”
Section: Phosphorescence Of Unsaturated and Aromatic Hydrocarbonsmentioning
confidence: 99%
“…The low-lying excited states of conjugated unsaturated and aromatic hydrocarbons are usually associated with delocalized π-electrons. , The role of radiative S ↔ T transitions in electron spectroscopy of conjugated hydrocarbons has been substantially less studied comparing with singlet states. Notably, the triplet states of polyenes play an important role in the spectroscopy of natural carotenes and synthetic electroactive polymers like polyfluorene , and polyphenylenevinylene . Particularly, Guha et al have shown that the triplet yields for ISC starting from low-lying singlet excited states for different polyenes are significantly increased (about three orders) with the increase of the polymer chain.…”
Section: Computational Phosphorescence Of Molecular Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 30 ] Time-dependent many body calculations show that in an electron-hole recombination process, the charge transfer and exchange pathways may result in the mixing of the triplet and excited singlet states, thus opening up the triplet-singlet ground state transition, which is typically forbidden. [ 31 ] Since the nanocomposite sample has a very low wt% of PF2/6, the 500 nm emission is weak. Barring some of the subtle differences between the pristine and the nanocomposite sample, both PL and EL spectra are almost identical for the two samples.…”
Section: Ff:pf2/6 Nanocompositementioning
confidence: 99%